The role of the State in the urban development of Budapest - Keresztély, Krisztina (Discussion Papers, 2012)
What is the effect of globalisation on nation states? Will they ‘disappear’? To what extent will national governments lose influence in the face of ever more influen¬tial supranational organisations? Will nation states remain the basic units of the world political and economic structures and will central governments keep their traditional decision-making powers? Although nation states have maintained themselves, one nonetheless observers a fundamental weakening of their position. They have lost the ‘monopoly’ of decision-making power in the political and eco¬nomic arenas: ‘while the nation state is far from being finished, there is a good reason to doubt that states hold the monopoly of power within the politics of glob-alisation. The end of the monopolistic position of central governments generates new methods of public intervention, which strengthens the role of differ¬ent types of public/private co-operation. These reflect the restructuring of public intervention and public investment in the urban development of metropolitan areas. While globalisation has a weakening effect on nation states and on their central governments, it has a strengthening effect on the development of large urban areas. Large cities serve as headquarters for global (multinational) enterprises, become the nodes of global economic processes, and accommodate new urban functions and urban hierarchies. How do the new international (global) roles of capital cities influence their po¬sition against the central government? At the beginning of the 1990s, in Budapest, the combined effects of political transition and of globalisation fundamentally changed the status of the capital within the nation state. This transformation reflected the lack of economic, political and social stability that emerged in the wake of political transition. The aim of our study is to analyse how the traditional role of the central state has been transformed in the urban development of Budapest. In section one, the new and reinforced central position of the capital and its effects on the general political atmosphere will be considered. In section two, the retreat of the state from the fields of urban management and policy-making (administration, taxation) will be described. In the final section, new forms of state investment and intervention in urban development will be analysed on the basis of two case studies of important, state-initiated urban projects in Budapest.